Multilocus Sequence Typing for Candida albicans Isolates from Candidemic Patients: Comparison with Southern Blot Hybridization and Pulsed-field Gel Electrophoresis Analysis - Myoung, Youn (The Korean Society for Laboratory Medicine, 2011)
BACKGROUND: We evaluated the efficacy of multilocus sequence typing (MLST) for assessing the genetic relationship among Candida albicans isolates from patients with candidemia in a hospital setting. METHODS: A total of 45 C. albicans isolates from 21 patients with candidemia were analyzed. The MLST results were compared with results obtained by Southern blot hybridization (C1 fingerprinting) and pulsed-field gel electrophoresis (PFGE). PFGE analysis included karyotyping and restriction endonuclease analysis of genomic DNAs using BssHII (REAG-B) and SfiI (REAG-S). RESULTS: The 45 isolates yielded 20 unique diploid sequence types (DSTs) by MLST, as well as 12 karyotypes, 15 REAG-B patterns, 13 REAG-S patterns, and 14 C1 fingerprinting types. Microevolution among intra-individual isolates was detected in 6, 5, 3, 5, and 7 sets of isolates by MLST (1 or 2 allelic differences), REAG-B, REAG-S, C1 fingerprinting, and a combination of all methods, respectively. Among 20 DSTs, 17 were unique, and 3 were found in more than 1 patient. The results of 2 DSTs obtained from 9 patient isolates were in agreement with REAG and C1 fingerprinting patterns. However, the remaining DST, which was shared by 2 patient isolates, showed 2 different PFGE and C1 fingerprinting patterns. In addition, 3 sets of isolates from different patients, which differed in only 1 or 2 alleles by MLST, also exhibited different PFGE or C1 fingerprinting patterns. CONCLUSIONS: MLST is highly discriminating among C. albicans isolates, but it may have some limitations in typing isolates from different patients, which may necessitate additional analysis using other techniques.